TV SHOWS THE WORLD FREEDOM AS THE BERLIN WALL FALLS : An Augmented Reading Experience - Smith-Llera, Danielle , 1971- (CPB grades 4-8. Captured television history 4D, 2019)
"On-point historical photographs combined with strong narration bring the story of the Berlin Wall to life. Kids will learn about the partition of Berlin after WWII, the cold war tensions between the US and the USSR that led to the building of the wall, and the anti-communist pressures that led it to fall. The fall of the wall would become a symbol of democracy and freedom. Readers will understand the significance behind this event through text and clips of the event itself via the Capstone 4D augmented reality app"